Propuestas del Banco Mundial para la educación en América Latina: un análisis crítico desde los principios filosóficos de la educación - Raquel, Raquel (Cauriensia, 2023)
This study aims to critically analyze, from the philosophical principles of education, the proposals of the World Bank for education in Latin America and the Caribbean after the context known as the "lost decades" in the dictatorships and the Latin American foreign debt resulting from this years. The central aspects studied in this article refer to the context of educational policies in Latin America and the Caribbean since the 1980s, the new social and educational proposals of the World Bank and the International Monetary Fund. Finally, it is identified that these have led to a systematic transgression of the philosophical principles of inclusion, quality, diversity and democracy in education, for which the need to strengthen these aspects in attention to the continuous educational challenges in the political context is highlighted. current neoliberal.